العوامل المؤثرة في اختيار السائح للوجهة السياحية -دراسة ميدانية على عينة من السياح الجزائريين-: The Factors Influencing the Choice of the Tourist Destination -The Field Study on a Sample of Algerian Tourists- - عامر هوام (Journal of North African Economies, 2025)
This study aims to test the impact of the various external and internal factors influencing the choice of tourist destination. In order to test that, a comprehensive survey was conducted using a questionnaire. The questionnaire forms are distributed to the random sample made up of 500 Algerian tourists, and 465 forms were retrieved for the statistical analysis by a SPSS V28 program. The results of this research showed that there is statistically significant effect of those factors on tourist where he chooses the destination, The correlation coefficient between the variables reached 0.529, which refers to the existence of a positive relationship and strong direct link. The Tourist selected the destination is due mainly to the various factors that are introduced by this investigation with a rate of 27.90 % among the overall factors. Therefore, this research recommends that science of tourism behavior should be considered in order to formulate the marketing strategy for realizing in the best conditions.